Reproducción y alimentación del gaspar Atractosteus tropicus (Pisces : Lepisosteidae) en el Refugio Nacional de Vida Silvestre Caño Negro, Costa Rica - Mora Jamett, Margarita; Cabrera Peña, Jorge; Galeano M, Geovanny (Revista de Biología Tropical, 1997)
Reproduction, length-wejght rdationship, amI food habí!s of gllr AtraclOsleus tl'Opicus were studíed in streams and ponds of National Wildlífe Refuge Caño Negro, Costa Rica from February 1990 through February 1991.Sex ratio was 0.97 wilh preponderan ce of femules, especially in lhe ¡arges! síze-classes. Macroscopic and microscopic exarnination of gonads indicate a single, distinct reproductive season fram April lo October during lhe wet season. The mean síze at maturity for males :me! females was 50-60 cm total length. Fecundity was 1.124 - 99. 087 eggs per ripe female and i! is linearly related to fish length ane! body weight by the equations: F = 1150.6 length - 74130.6 and F = 8.59 weight - 7485.6. The total length-weight regressionwas !oglO weight= -2.964 + 3.351 ¡oglo lenglh for males , ane! loglO weight = -2.729 + 3.211 loglo length for females. The dominant groups found in the stomachs were Cichlidae, Poeciliidae, Characidae, Pi.melodidae, Gymnotidae ane! crustaceans, in order of decreasing importance.